One-dimensional wavelet and reanalysis of gravity waves - Can, Z; Aslan, Z; Oguz, O (SPRINGER HEIDELBERG, 2004)
Different meteorological parameters and atmospheric circulations are known as one of the sources of excitement of gravity waves (GWs). The main purpose of this paper is to analyze the GWs and seasonal variations over Istanbul by wavelet-based computer simulations. Turbulent structures of pressure, height, and air temperature have been analyzed in this paper. These waves are in the meso-scale wave-form and, generally, are observed in spring, autumn, and winter. The FAWAV Wavelet software and the latest version of MATLAB wavelet packet are applied to analyze meteorological parameters for the north-western part of Turkey. Wavelet based computer simulation of data is generally close to the real data under consideration for the Daubechies wavelet series.
Keywords: gravity waves; wavelet transform; Daubechies wavelet; TEMPERATURE; PRESSURE; Science & Technology - Other Topics